Urgensi Perlindungan Pulau-Pulau Terluar Dalam Kaitan Integritas Teritorial Indonesia - Erwin (Law Faculty of Universitas Bandar Lampung, 2011)
A territory is an essential element and most important for a country. Territory become important for the country with respect .for state sovereignty within the limits of the jurisdiction of the state that can be implemented. Archipelagic State is one type of state based on territorial coverage. Indonesia as a large Archipelagic State should be able to maintain the integrity of its territory. There are about 17,506 islands owned by Indonesia, the number of outer islands there is a direct border with neighboring Indonesia. The condition become urgent in an integrated management of the outer islands, with the aim to demonstrate the integrity of the Unitary of Republic of Indonesia. This is due to the importance of the islands, in general there are three points of view ie as a function of defense and security, economic, and ecological functions.